Toplu konut dış mekan kalitesi standartları (Örnek: Ataköy 9-10 kısım analiz çalışması) - Temurlenk, Meral (Fen Bilimleri Enstitüsü, 1997)
İnsanlar, toplu konutlarda yaşamsal kalitesi yüksek çevrelerde yaşamayı hedeflemektedir. Toplu konut, ünitelerinin belli ölçülere göre bir komşuluk birimi yada böyle bir birimin bir kesimini meydana getirebilecek büyüklükte bir alan üzerinde yerleşen insanların barınma ihtiyaçlarını karşılayan binaların tümü ve bunlarla ilgili sosyal tesislerdir. Bu çalışmada toplu konutlarda dış mekan kalitesi standartları ele alınmaktadır. Birinci bölümde, araştırmanın amacı ve konusu anlatılmaktadır. İkinci bölümde, toplu konut standartları açıklanarak, toplu konut dış mekan kalitesi standartları, kentsel dış mekan kalitesi ile ilişkinlendirerek ele alınmaktadır. Üçüncü bölümde yaşamsal kalite, çevresel kalite kavramları açıklanarak, kentsel mekan kalitesi ve toplu konut dış mekan kalitesinin özellik, fonksiyon, nitelik ve sınıflandırılmaları anlatılmaktadır. Toplu konut kullanım sonrası değerlendirme çalışmaları modelleri ve sonuçları açıklanmaktadır. Dördüncü bölümde, Rapoport' un sınıflandırdığı konut dış mekan kalitesi nitelikleri ele alınarak, bu konuda, niteliksel ve niceliksel standartlar ortaya konmaktadır. Dördüncü bölümün sonunda, Türkiye' de toplu konutlarda çevresel kalite sorunu ve bu soruna ilk çözümsel yaklaşımlar yapmış olan T.C. Emlak Bankası'nın çalışmaları konusu ele alınmaktadır. Beşinci bölümde Ataköy 9-10. kısımda toplu konutlarda çevresel kalite konusunda bir analiz ve anket çalışması yapılmıştır. Sonuçlar tez konusu olan, toplu konutlarda çevresel kalitenin önemini ve çevresel kalite standartları getirmek gerekliliğini ortaya koymaktadır. Altıncı bölümde, toplu konutlarda çevresel kalitenin nitelik ve niceliklerine yönelik standartlar için sonuçlar ve öneriler getirilmektedir

The aim of the research is to make clear the importance of the fact that outdoor design, which is a continuation of a house, should reach the outdoor standards, with the aim of reaching a certain environmental quality. The targetid to plan, to project, and to build houses that present livable environment, not as isolating the house from environment, but as a part of urban environment. Mass housing is all of the buildings which meet the need for residence of the people who dwell in an area which is big enough to make up an unit of neighborhood according to specific standards or which is big enough to make up a part of such an unit and a social facilities of these buildings. House is the place that becomes a whole with human and meets his need of sheltering. The house, one lives in, is the limit of his sovereignty in either his private life or his daily life. House is not only a place that one spends his life in, but also a life unit that exists with his social relationships in socio-cultural meaning. For this reason, a house also exists with the near environment out of its walls. House should provide people minimum life standard by its indoor and near environment. Generally housing problems is seen in big cities. In these cities, illegal buildings fields (squatter) cause to increase housing problems. In developing countries such as Turkey, sheltering problem is tried to solve by mass housing that means minimum standards and low cost In this case, house is a part of mass housing beyond being a unit It should make a whole with urban environment that it exists in, since it gets an urban project meaning beyond its architectural meaning. Therefore, life quality and standards should be researched in either people's or houses' dwelling. Political lines and strategies should be determined by a totalitarian observation on events. For this reason, to form human surroundings out of house's own physical restriction; some sanctions should be brought; some research should be XIV done on house outfield standards that are arranged depending on house; house out of fields should be taken into consideration. In this subject, investment and controlling practice also brings some standards and some criteria related with use of outdoor fields. These criteria and standards should be grouped as fields use such as sport, environment, and rest; forming open places; social relationships arranging units; urban furniture and objects; using of green field; choosing and using of upholstery equipment. It is an aim of urban project to provide people living in mass housing live in an environment that meets their physical, visual, psychological and social needs; in order with high standards. In urban dwelling, it depends on definite standards to form better living environments. In this study, some results on arranging outdoor places have been made up by some theoretical and analytic studies, so as to determine outdoor places' standards. The concept of mass housing and its standards were taken into consideration. Mass housing is a medium of sheltering with low cost; proper to health conditions; which is enable to meet people's need in minimum dimensions and quality. Some information was given about house, mass-housing definition, Turkey's need of mass housing, housing policy, housing classification produced in urban fields. These informations show the development of housing policy and its present situation. In housing standards concept, standard definition and its aim are given by explaining what housing standards mean, its position in project, using aim and its importance. The criteria for determination of quality and quantity of house are planning problem as process and product The aims are to increase the house production, to decrease the cost, to obtain the maximum degree of product and to protect the user by preventing waste of source. Restriction brought to housing standards in Turkey and the influence degree of the society that determines the standards were observed. In this way, some information was given about the fact that what kind of restriction you can face so as to from outdoor xv 6. Having taken into consideration practice of landscape design and urban furniture. To be researched environmental quality, a questionnaire study was applied in Ataköy section 9. 10.. Question Form in the Questionnaire Section I- recognition of person and family Section II- recognition of house and house using Section III- recognition of the social habits of users Section IV- recognition of the wishes, critic, satisfaction and preferences of user These four sections are aimed to reach in the questionnaire Questionnaire results show the importance of environmental quality. As a result, in mass housing project, standards and criteria about urban outdoor places should be researched, determined housing policy and control mechanism which is proper to research result, should be formed, mass housing practice with high life standards should be realized. xvm done on house outfield standards that are arranged depending on house; house out of fields should be taken into consideration. In this subject, investment and controlling practice also brings some standards and some criteria related with use of outdoor fields. These criteria and standards should be grouped as fields use such as sport, environment, and rest; forming open places; social relationships arranging units; urban furniture and objects; using of green field; choosing and using of upholstery equipment. It is an aim of urban project to provide people living in mass housing live in an environment that meets their physical, visual, psychological and social needs; in order with high standards. In urban dwelling, it depends on definite standards to form better living environments. In this study, some results on arranging outdoor places have been made up by some theoretical and analytic studies, so as to determine outdoor places' standards. The concept of mass housing and its standards were taken into consideration. Mass housing is a medium of sheltering with low cost; proper to health conditions; which is enable to meet people's need in minimum dimensions and quality. Some information was given about house, mass-housing definition, Turkey's need of mass housing, housing policy, housing classification produced in urban fields. These informations show the development of housing policy and its present situation. In housing standards concept, standard definition and its aim are given by explaining what housing standards mean, its position in project, using aim and its importance. The criteria for determination of quality and quantity of house are planning problem as process and product The aims are to increase the house production, to decrease the cost, to obtain the maximum degree of product and to protect the user by preventing waste of source. Restriction brought to housing standards in Turkey and the influence degree of the society that determines the standards were observed. In this way, some information was given about the fact that what kind of restriction you can face so as to from outdoor xv 6. Having taken into consideration practice of landscape design and urban furniture. To be researched environmental quality, a questionnaire study was applied in Ataköy section 9. 10.. Question Form in the Questionnaire Section I- recognition of person and family Section II- recognition of house and house using Section III- recognition of the social habits of users Section IV- recognition of the wishes, critic, satisfaction and preferences of user These four sections are aimed to reach in the questionnaire Questionnaire results show the importance of environmental quality. As a result, in mass housing project, standards and criteria about urban outdoor places should be researched, determined housing policy and control mechanism which is proper to research result, should be formed, mass housing practice with high life standards should be realized.
Environmental Quality standards in mass housing case study: Ataköy, 9. 10. section
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Sosyal Bilimler Enstitüsü, 1997
Keywords: Bina bilgisi; Dış mekan; Toplu konutlar; Building information; Outdoor; Mass houses